AuNP‐Modulated qPCR: An Optimized System for Detecting MIR Biophotons Released in DNA Replication. Issue 8 (12th January 2023) - Yang, Yu; Peng, Daoling; Gu, Zhenglong; Jiang, Lei; Song, Bo
Abstract: Living systems can utilize energy with a high efficiency. Biophotons are proposed to modulate biological functions with such efficiency; however, the underlying mechanism remains unexplored, especially due to the challenge of ultraweak mid‐infrared (MIR) light detection and the theoretical perturbation from spontaneous MIR emission. Here, we proposed an optimized system to detect MIR biophotons generated in the hydrolysis of deoxynucleotide triphosphates (dNTPs, energy‐storing molecules similar to ATP). The system used a quantitative polymerase chain reaction (qPCR) that was modulated by gold nanoparticle (AuNP) concentration and thus by the inter‐AuNP distance, which depends on the concentration above. The measurements indicate that 33‐ and 84‐THz photons are released by dNTP hydrolysis, which can drive DNA replication. Our findings provide a novel chain‐reaction‐based method for detecting MIR photons in solution, and pave a way for photon‐based insights to understand the highly efficient energy utilization of biology. Abstract : Living systems utilize energy with a high efficiency, but the mechanism remains unclear. Our detection based on an AuNP‐modulated qPCR system shows that 33‐ and 84‐THz photons are released by the hydrolysis of dNTP (an energy‐storing molecule like ATP), which efficiently drives DNA replication. Our findings provide a novel method for detecting MIR photons, and pave a way for photon‐based insights to understand the high‐efficiency energy utilization of biology.